The impact of moral injury on healthcare workers’ career calling: exploring authentic self-expression, ethical leadership, and self-compassion - Feifei Li; Lei Sun; Fanli Jia (BMC Medical Ethics)
Abstract Background Moral injury is a significant issue for healthcare workers, often stemming from exposure to ethical dilemmas and distressing events. This study aims to explore the relationship between moral injury and healthcare workers’ career calling, using the job demands-resources model as a theoretical framework. The goal is to understand how moral injury affects healthcare workers’ sense of purpose and vocation and identify factors that may mitigate this impact. Methods A cross-sectional survey was conducted with a sample of 506 Chinese healthcare workers. The study used self-report questionnaires to assess moral injury, authentic self-expression, self-compassion, ethical leadership, and career calling. Path analysis was used to test the proposed mediating and moderating relationships within the job demands-resources model. Results Moral injury has a negative effect on healthcare workers’ career calling. This effect is mediated by authentic self-expression – the inability to openly discuss moral distress weakens the sense of purpose. Self-compassion and ethical leadership buffer against the negative impact of moral injury on career calling. Conclusions This research contributes to the understanding of moral injury and career calling in healthcare workers, with practical implications for safeguarding healthcare professionals’ well-being and commitment to their vocation.